REVISITING GREEN SUPPLY CHAIN MANAGEMENT THROUGH MEDIATION OF SOCIAL CAPITAL: A RESEARCH DIRECTION - Che Sobry, Suheil; Nor A'zam, Muhammad Khairul Zharif; Ismail, Muhammad Saiful Islam; Rozali, Norhasyikin; Hanafi, Ahmad Harith Ashrofie; Abidin, Rahimi (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
Green supply chain management (GSCM) has emerged as a crucial strategic approach for manufacturing companies to achieve sustainable performance as environmental regulations become more stringent and stakeholder expectations rise. Despite its growing adoption, the relational mechanisms that enable GSCM practices to effectively translate into measurable sustainability outcomes remain insufficiently explored. By proposing social capital with structural, relational, and cognitive components as a mediating mechanism, this paper re-examines the relationship between GSCM and sustainable performance. This study creates a thorough conceptual framework that demonstrates how embedded social relationships within supply chain networks strengthen green supply chain practices through underpinning theories of Natural Resource-Based View (NRBV) and Social Capital Theory (SCT). These social interactions facilitate knowledge sharing, trust, and collective commitment, which in turn enhance economic, environmental, and social performance outcomes. To empirically validate the proposed model, this study adopts a quantitative research design targeting firms in the Electrical and Electronics (E&E) manufacturing sector. The paper contributes to the literature by extending the understanding of GSCM from a predominantly techno-operational perspective to a socio-operational perspective, highlighting the importance of social capital in strengthening the effectiveness of green supply chain initiatives. The findings are expected to provide valuable managerial insights for fostering trust, shared vision, and collaborative networks to support sustainable supply chain transformation.